2014
DOI: 10.2308/accr-50871
|View full text |Cite
|
Sign up to set email alerts
|

Does Internal Audit Function Quality Deter Management Misconduct?

Abstract: Standard-setters believe high-quality internal audit functions (IAFs) serve as a key resource to audit committees for monitoring senior management. However, regulators do not enforce IAF quality or require disclosures relating to IAF quality, which is in stark contrast to regulatory requirements placed on boards, audit committees, and external auditors. Using proprietary data, I find that a composite measure of IAF quality is negatively associated with the likelihood of management misconduct even after control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
115
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(131 citation statements)
references
References 35 publications
8
115
2
6
Order By: Relevance
“…The findings agree with the resource-based theory that competencies, skills and capabilities of human resource within an organization are critical for organizational performance (Barney, 2001). Also, the study supports Ege (2015) that the quality of internal audit can deter management excesses and contribute to the health of the organization. Thus, the higher the internal audit characteristics, the more the contribution to improved performance of an organization.…”
Section: Regression Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The findings agree with the resource-based theory that competencies, skills and capabilities of human resource within an organization are critical for organizational performance (Barney, 2001). Also, the study supports Ege (2015) that the quality of internal audit can deter management excesses and contribute to the health of the organization. Thus, the higher the internal audit characteristics, the more the contribution to improved performance of an organization.…”
Section: Regression Resultssupporting
confidence: 86%
“…These characteristics enable the internal audit function to add value to an organization through their unique part in governance, risk, and control. Also, these characteristics determine the extent and perception of the quality of an internal audit function (Ege, 2015;Hutchinson & Zain, 2009). A number of studies have found significant relationships between these characteristics and effectiveness of internal audit (Arena & Azzone, 2009;Cohen & Sayag, 2010).…”
Section: Internal Audit Characteristics and Performancementioning
confidence: 99%
“…By the IIA's definition, internal audit should bring a ''systematic, disciplined approach to evaluate and improve the effectiveness of risk management, control, and governance processes'' (IIA, 2011a). Standards for the internal auditing profession affirm the IAF's responsibility to monitor financial reporting (e.g., IPPF, 2012) and help detect and deter fraud (e.g., IIA, 2009b;IPPF, 2012), as well as reduce related losses (Coram, Ferguson, & Moroney, 2008;Ege, 2015;KPMG, 2003;Norman et al, 2010).…”
Section: Iaf Quality and Financial Reporting Qualitymentioning
confidence: 99%
“…While this spectrum of rotational programs exists in practice, prior academic literature has focused on the first two types of programs and examined how internal auditors' ultimate goal of obtaining a management position outside of internal audit likely impacts his/her effectiveness as an internal auditor. Both academics and practitioners refer to these types of rotational programs as ''management training grounds'' (i.e., MTGs) because one of their main purposes is developing future managers' skills by working in internal audit (e.g., Burton, Starliper, Summers, & Wood, 2015;Ege, 2015;IIA, 2013;Messier et al, 2011;Rose et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation